The perceived impact of project ECHO networks in Northern Ireland for health and social care providers, patients, and the health system: A qualitative analysis. (1st November 2022) - Jenkins, Chris; Diffin, Janet; McTernaghan, Tracey; Watson, Max; Fleming, Kate
This study assesses the perceived impact and benefits of Project ECHO (Extension for Community Healthcare Outcomes), a tele-mentoring intervention for health and social care providers, patients and the health system in Northern Ireland. Having access to a specialist, a space to share experiences, and being able to disseminate up-to-date best practice were all cited as improving provider knowledge as well as improving quality of care for patients. Healthcare providers reported being more confident in managing patients and that relationships had been improved between different levels of the health system. ECHO was described as improving access to education and training by removing geographic and time barriers. This is one of the first studies to qualitatively analyse impact across a number of different clinical and social care ECHO networks. The results strongly indicate the perceived benefit of ECHO in improving provider, patient and health system outcomes such as increased healthcare provider knowledge and confidence to manage patients at primary levels of the health system. This has implications for future service design, particularly within the context of COVID-19 in which virtual and online training is necessitated by social distancing requirements.